2006
DOI: 10.1111/j.1365-2621.2006.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of fresh, sun‐ and sulphited‐dried Malatya apricot (Prunus armeniaca) assayed by CUPRAC, ABTS/TEAC and folin methods

Abstract: Apricots as five varieties of Malatya region have been assayed as fresh, sun-and sulphited-dried samples, using the antioxidant capacity measurement methods Cupric Ion Reducing Antioxidant Capacity (CUPRAC) and 2,2¢-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), and total polyphenol measurement method Folin. The novel reagent for the CUPRAC total antioxidant capacity assay, bis(neocuproine)copper(II) chloride, was easily accessible, stable, selective and responding to all antioxidants. Sulphite (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 40 publications
(64 reference statements)
0
18
0
2
Order By: Relevance
“…Changes in antioxidant activity and redox potential after processing Some authors have correlated the presence of phenolics with antioxidant activity in apricots [22,38]. Our assays of antioxidant capacity, conducted with an electron transferbased antioxidant capacity assay, gave particularly interesting results.…”
Section: Phenolic Composition Of Fresh Fruits and Changes After Dryingmentioning
confidence: 76%
See 1 more Smart Citation
“…Changes in antioxidant activity and redox potential after processing Some authors have correlated the presence of phenolics with antioxidant activity in apricots [22,38]. Our assays of antioxidant capacity, conducted with an electron transferbased antioxidant capacity assay, gave particularly interesting results.…”
Section: Phenolic Composition Of Fresh Fruits and Changes After Dryingmentioning
confidence: 76%
“…The literature does not clearly explain the effect of drying on the phenolic content and antioxidant activity of apricot fruit. Güclü et al [22] reported a new spectrophotometric method (CUPRAC) for the assay of total antioxidant activity of fresh and dried (sun and sulphited) apricots. This paper revealed an increase in antioxidant activity (even if the authors refer the data to gram of solid matter, it is not well clear if they meant dry matter), but did not consider the fate of single polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…In a wide-range screening study (Ishiwaba, Yamaguchi, Takamura, & Matoba, 2004), 25 fruits were investigated for their antiradical activity against DPPH and the highest scavenging activity was observed in hawthorn, apricot, and blueberry. Apricots from five varieties growing in Malatya region (Turkey) classified as fresh, sun-and sulphited-dried samples were tested for their antioxidant activity using cupric ion-reducing antioxidant capacity (CUPRAC) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) methods (Guclu, Altun, Ozyurek, Karademir, & Apak, 2006). The samples exerted a high antioxidant activity whose results obtained from CUPRAC method were well-correlated with those of ABTS.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…El contenido de antocianinas se determinó por el método diferencial de pH según el método propuesto por Wrolstad, 1976 y se expresó como mg de cianidina-3-glucosido/L, el contenido de Fenoles totales se determinó por el método de Folin y la Capacidad antioxidante por los métodos: CUPRAC (reducción del ion cúprico) , y ABTS (captura del radical catión del ácido 2,2'-azino-bis-(3-etillbenzotiazolin-6-sulfonico), según lo señalado por Guclu et al, 2006. Se empleó Trolox (ácido (±)-6-hidroxi-2,5,7,8-tetrametil-croman-2-carboxílico) como estándar en la elaboración de las curvas de calibración.…”
Section: Análisis Químicosunclassified